Angiotensin-converting enzyme inhibitors - David García Barreto; Alberto Toruncha Chuckram (ECIMED, 2014)
In an updated review concerning the angiotensin-converting enzyme inhibitors, an account of the historical development of this group of drugs proved as highly effective in the treatment of hypertension and of congestive heart failure is made. We review the action mechanism of ACEI, emphasizing not only their capacity to inhibit angiotensin II actions, but also to potentiate Bradykynin effects. The action mechanism in hypertension and congestive heart failure is also reviewed as well as its possible anti-anginal and anti-sclerotic effects. We also analyze the nephroprotection achieved by ACEI and show the classification of the 3 chemical groups related to these drugs so as to perform a detailed revision of the ACEI therapeutic trials associated to hypertension, myocardial infarction and heart failure. Other possible ACEI therapeutic benefits still under an experimental phase are exposed as well as the adverse effects described in the medical literature. To conclude, a brief analysis of the treatment cost of this drug group is stated.